Cardiac computed tomography previous to atrial fibrillation ablation - effects of technological improvements and protocol optimization - Pinto Marques, Hugo (2018)
Copyright © 2018 Sociedade Portuguesa de Cardiologia. Publicado por Elsevier España, S.L.U. All rights reserved.